2022
DOI: 10.1021/acs.jpcb.2c04181
|View full text |Cite
|
Sign up to set email alerts
|

G-Tetrad-Selective Ligand Binding Kinetics in G-Quadruplex DNA Probed with Fluorescence Correlation Spectroscopy

Abstract: Probing the kinetics of ligand binding to biomolecules is of paramount interest in biology and pharmacology. Measurements of such kinetic processes provide information on the rate-determining steps that control the binding affinity of ligands to biomolecules, thereby predicting the mechanism of the molecular interaction. In this context, ligand binding to G-quadruplex DNA (GqDNA) structures has attracted tremendous attention primarily because of their use in possible anticancer therapy. Although a large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Since TEGPy might exhibit multiple binding modes towards the ILPR G4, the enhanced binding strength compared to TMPyP4 may be attributed to the additional binding, i.e., loop or groove binding. According to a recent study involving fluorescence correlation spectroscopy [33], TMPyP4 is indicated to bind slightly stronger to the 5 ends of human telomeric DNA sequences than to the 3 ends used in the present study (by a factor of ca. 7, albeit with quite a large uncertainty).…”
Section: Absolute Binding Free Energies For the Ilpr G4-ligand System...mentioning
confidence: 65%
“…Since TEGPy might exhibit multiple binding modes towards the ILPR G4, the enhanced binding strength compared to TMPyP4 may be attributed to the additional binding, i.e., loop or groove binding. According to a recent study involving fluorescence correlation spectroscopy [33], TMPyP4 is indicated to bind slightly stronger to the 5 ends of human telomeric DNA sequences than to the 3 ends used in the present study (by a factor of ca. 7, albeit with quite a large uncertainty).…”
Section: Absolute Binding Free Energies For the Ilpr G4-ligand System...mentioning
confidence: 65%
“…The second hypothesis suggests that inefficient fluorescence quenching in the case of 3Ei might be due to a difference in redox potentials of the N ‐benzylpyridinium groups in 3Ei versus N ‐methylquinolinium groups in 3Ab , 3Cb , 3Ef , and PhenDC3. As the quenching of the reporter fluorophore by the ligand is most plausibly due to the oxidative photoinduced electron transfer (PeT) process,[ 38 , 75 ] ligands with low reduction potential would perform as poor quenchers in this assay; thus, it is possible that the reduction potential ( E red ) of N ‐benzylpyridinium substituents in 3Ei is not sufficient to quench the fluorescence of Cy5. Indeed, a simple comparison of reduction potentials of isolated N ‐methylpyridinium ( E red =−1.32 V) and N ‐methylquinolinium cations ( E red =−0.96 V) [76] gives evidence that oxidative PeT is less energetically favorable with N ‐methylpyridinium cation as a quencher (by 8.3 kcal mol −1 , all other parameters being equal).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence correlation spectroscopy (FCS), which calculates the temporal correlation of fluorescence intensity fluctuations [1,2], is a powerful and versatile method for detecting and characterizing fluorescent molecules. FCS performs significant advantages in measuring diffusion coefficients, chemical rate constants, concentration, aggregation, and rotational dynamics, and thus has been applied in various fields including biology, physiology, pharmacology, and environmental sciences [3][4][5][6][7]. Despite it has showcased the measurement abilities in rapid speed, small sample volume, high sensitivity, and ultra-low detection limit [8,9], it has seen limited adoption outside the research laboratory, especially in-situ detection.…”
Section: Introductionmentioning
confidence: 99%